Kinerja Keuangan Perbankan Swasta Nasional Indonesia Sebelum dan Setelah Krisis Ekonomi - Surifah Surifah (Jurnal Akuntansi dan Auditing Indonesia, 2002)
The aim of this study is to analyze the performance of the private banks in Indonesia before and after the economic crisis. The results of the study could be useful for those who are concerned with the healthiness and the performance of the banks.The study involved thirty-two private banks selected from the Indonesian banking Directory using purposive sampling method. From the directory, the researcher also collected the annual financial reports of the sample banks from 1994 through 1999.A number of statistical tools were used for data analyses including the data normality test, the Mann-Whitney U test, and the independent t-test. Results indicated that all variables, except for management leverage, are not normally distributed. The Mann-Whitney test suggested that while significant differences exist in the average ratio of capital, assets, management, and liquidity between the two periods, there was no significant difference in the average ratio of earnings and profitability. Most ratios were higher after crisis period than before one. The independent t-test supported most of these findings. It demonstrated that whereas significant differences exist in the ratios of productive assets quality, management, and liquidity, there were no significant differences in the earnings ratios.